Pelestarian Indang Melalui Pemberdayaan Masyarakat di Korong Kuliek Nagari Sungai Buluh Timur - Marfalak, Marfalak (Universitas Nusa Cendana, 2022)
Empowerment is an effort and effort in giving strength to the community in utilizing the potential and being able to make the community independent. The condition of the Korong Kuliek community is that there is a lack of interest and participation in the preservation of Indang. Therefore, the purpose of this article is to describe how to preserve indang through community empowerment in Korong Kuliek Nagari Sungai Buluh Timur. Apart from this, this article also tries to see how the Korong Kuliek community is helpless towards Indang conservation. In writing this article, the study uses literature relating to the methods of collecting library data, reading and taking notes, and managing research materials (Zed, 2008:3). The results of the research study explain that community empowerment through the preservation of indang culture is able to have a positive impact on the community. With the preservation of the Indang dance in Korong Kuliek Nagari Sungai Buluh Timur, the culture of the area will continue to be maintained and sustainable. The most important thing in this empowerment is the participation of the government, community leaders, and local communities. Because in principle the community plays an important role in the preservation of this indang.